Contemporary evolution of the innate immune receptor gene TLR3 in an isolated vertebrate population. Issue 11 (5th May 2021) - Davies, Charli S.; Taylor, Martin I.; Hammers, Martijn; Burke, Terry; Komdeur, Jan; Dugdale, Hannah L.; Richardson, David S.
Abstract: Understanding where genetic variation exists, and how it influences fitness within populations is important from an evolutionary and conservation perspective. Signatures of past selection suggest that pathogen‐mediated balancing selection is a key driver of immunogenetic variation, but studies tracking contemporary evolution are needed to help resolve the evolutionary forces and mechanism at play. Previous work in a bottlenecked population of Seychelles warblers ( Acrocephalus sechellensis ) show that functional variation has been maintained at the viral‐sensing Toll‐like receptor 3 ( TLR3) gene, including one nonsynonymous SNP, resulting in two alleles. Here, we characterise evolution at this TLR3 locus over a 25‐year period within the original remnant population of the Seychelles warbler, and in four other derived, populations. Results show a significant and consistent temporal decline in the frequency of the TLR3 C allele in the original population, and that similar declines in the TLR3 C allele frequency occurred in all the derived populations. Individuals (of both sexes) with the TLR3 CC genotype had lower survival, and males ‐ but not females ‐ that carry the TLR3 C allele had significantly lower lifetime reproductive success than those with only the TLR3 A allele. These results indicate that positive selection on the TLR3 A allele, caused by an as yet unknown agent, is driving TLR3 evolution in the Seychelles warbler. No evidence of heterozygote advantage was detected. However, whether the positive selection observed is part of a longer‐term pattern of balancing selection (through fluctuating selection or rare‐allele advantage) cannot be resolved without tracking the TLR3 C allele over an extended time period.